2010
DOI: 10.1111/j.1476-5381.2009.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

GPR55 ligands promote receptor coupling to multiple signalling pathways

Abstract: Background and purpose: Although GPR55 is potently activated by the endogenous lysophospholipid, L-alysophosphatidylinositol (LPI), it is also thought to be sensitive to a number of cannabinoid ligands, including the prototypic CB1 receptor antagonists AM251 and SR141716A (Rimonabant ® ). In this study we have used a range of functional assays to compare the pharmacological activity of selected cannabinoid ligands, AM251, AM281 and SR141716A with LPI in a HEK293 cell line engineered to stably express recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
200
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 26 publications
9
200
0
Order By: Relevance
“…In some studies, SR141716A is reported to be an inhibitor (6), and in other studies, the compound is reported to be an agonist of GPR55 (5,13,14). This is of major importance as SR141716A (Rimonabant) was widely prescribed to patients as an anti-obesity agent and was withdrawn because of mental health issues.…”
Section: Structural Analogues Of Sr141716a Inhibit Lpi-induced Activamentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, SR141716A is reported to be an inhibitor (6), and in other studies, the compound is reported to be an agonist of GPR55 (5,13,14). This is of major importance as SR141716A (Rimonabant) was widely prescribed to patients as an anti-obesity agent and was withdrawn because of mental health issues.…”
Section: Structural Analogues Of Sr141716a Inhibit Lpi-induced Activamentioning
confidence: 99%
“…To date, certain arylpyrazole CB 1 receptor antagonists such as Rimonabant (also known as SR141716A or Acomplia) and AM251 have been reported to be GPR55 agonists (5,13,14). However, other groups have suggested that Rimonabant is a GPR55 antagonist (6,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, all the functions described so far for LPI on GPR55 come from experiments in which LPI was exogenously added to the cultured cells, and therefore evidence for the role of the naturally occurring lipid in more physiological settings is still missing. It has also been shown that several cannabinoid-type compounds modulate this receptor (Ryberg et al, 2007;Lauckner et al, 2008;WaldeckWeiermair et al, 2008;Henstridge et al, 2009Henstridge et al, , 2010Kapur et al, 2009;Yin et al, 2009). However, the inconsistencies among the pharmacological results obtained so far (some compounds being active in some reports and inactive in others, some being agonists in some studies and antagonists in others, and so on) do not entirely clarify whether GPR55 is an actual cannabinoid receptor (Brown and Robin Hiley, 2009;Ross, 2009).…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Conventional systems employ a stationary array of fiber optics to repetitively scan a microtiter plate. 12 As a result, only cells along the scanning path ͑ϳ100 m in width͒ are sampled to generate an averaged response.…”
mentioning
confidence: 99%